2018
DOI: 10.3389/fphys.2018.00374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Training on Extracellular Matrix Adaptations in Skeletal Muscle of Older Rats

Abstract: Accumulation of connective tissue, particularly extracellular matrix (ECM) proteins, has been observed in skeletal muscles with advancing age. Resistance training (RT) has been widely recommended to attenuate age-induced sarcopenia, even though its effects on the components that control ECM turnover in skeletal muscles remain to be elucidated. Thus, the aim of this study was to determine the effects of RT on connective tissue content and gene expression of key components of ECM in the skeletal muscles of aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Advancing age is associated with accumulation of ECM proteins in the skeletal muscle, 38 and we had previously reported excessive ECM deposition in the skeletal muscle of PyMT+ compared with wild-type mice. 16 Interestingly, similar increase in ECM deposition in the skeletal muscle was observed in Neu+ mice ( Figure 6C; bottom row).…”
Section: Neu+ Tumour-induced Dynamic Changes In Skeletal Muscle Strucmentioning
confidence: 77%
“…Advancing age is associated with accumulation of ECM proteins in the skeletal muscle, 38 and we had previously reported excessive ECM deposition in the skeletal muscle of PyMT+ compared with wild-type mice. 16 Interestingly, similar increase in ECM deposition in the skeletal muscle was observed in Neu+ mice ( Figure 6C; bottom row).…”
Section: Neu+ Tumour-induced Dynamic Changes In Skeletal Muscle Strucmentioning
confidence: 77%
“…de Sousa Neto et al (2018) reported that 12 weeks of resistance training consisting of ladder climbs with progressive, additional loads equivalent to 65-100% of each individual's maximum carrying capacity upregulated MMP-2 activity in the plantarflexor muscles of old rats, while down-regulating MMP-2 and MMP-9 in blood circulation. The authors' conclusion that resistance training might, therefore, be a useful tool to maintain ECM remodeling at older age has recently received empirical support by another training study in rats that used the same training protocol and showed a reduced deposition of connective tissue in trained older muscles (Guzzoni et al, 2018).…”
Section: Adaptations To Physical Training and Disusementioning
confidence: 99%
“…File 8). Importantly, some of these ECM/actin structural and remodelling genes have been shown to demonstrate increases after aerobic or resistance exercise at the gene expression, protein abundance or activity level such as; TIMP3 25 , FLNB 26 , COL4A1 27,28 , or are involved in satellite/muscle cell regulation (ITGB3 29 , CTTN 30 , LAMA5 31 , CRK 32,33 ). However, to the authors knowledge there is no evidence to suggest that any of these genes are differentially methylated at the DNA level in skeletal muscle anabolism or hypertrophy.…”
Section: Kegg Cancermentioning
confidence: 99%